2009
DOI: 10.1007/s10529-009-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

GroES and GroEL are essential chaperones for refolding of recombinant human phospholipid scramblase 1 in E. coli

Abstract: Human phospholipid scramblase 1(hPLSCR1), when expressed in E. coli (BL-21 DE3), forms inclusion bodies that are functionally inactive. We studied the effects of various stress inducing agents and chaperones on soluble expression of hPLSCR1 in E. coli (BL-21 DE3). Addition of 3% (v/v) ethanol before induction and decreasing the post-induction temperature to 15 degrees C increased the solubility of hPLSCR1 to approximately 10 and approximately 15% respectively. Presence of groES-groEL complex solubilized the hP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
7
1
1
Order By: Relevance
“…The addition of ethanol to the culture medium was tested for molecular chaperone induction and recombinant protein stabilization Baneyx 1996, 1997). In contrast with a previous study that showed an optimal ethanol concentration of 3% (Sahu et al 2009), yields from the present system were increased 2-fold after addition of 1% ethanol ( Figure 4D). To the best of our knowledge, this is the first report to demonstrate the effects of ethanol supplementation on CYP expression in E. coli.…”
Section: Discussioncontrasting
confidence: 99%
“…The addition of ethanol to the culture medium was tested for molecular chaperone induction and recombinant protein stabilization Baneyx 1996, 1997). In contrast with a previous study that showed an optimal ethanol concentration of 3% (Sahu et al 2009), yields from the present system were increased 2-fold after addition of 1% ethanol ( Figure 4D). To the best of our knowledge, this is the first report to demonstrate the effects of ethanol supplementation on CYP expression in E. coli.…”
Section: Discussioncontrasting
confidence: 99%
“…Trigger factor, on the other hand, associates with the synthesized proteins as soon as they leave ribosome and through its interaction with their exposed hydrophobic patches averts their subsequent aggregation [14], [38]. Co-expression of molecular chaperones resulted in enhanced solubility and production of recombinant rice plant catalase A [39] active ribonuclease inhibitor [40], human scramblase 1 [41] and zeta-crystallin [42]. Solubility of his-tagged ALDH3A1 was significantly improved under conditions of co-expressing the pG-KJE8) suggesting that dnaK/dnaJ/grpE and groES/groEL are the essential chaperones for the correct folding of recombinant human ALDH3A1 (his-tagged ALDH3A1) when over-expressed in E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…There is another degree of complication that the successful expression of the target gene in its desirable or soluble form still does not guarantee its activity. To overcome such difficulties and produce the target proteins successfully, various methods have been developed: strains capable of translating rare codons, strains capable of forming disulfide bonds intracellularly, plasmids with a specifically designed promoter, tags or fusion partners conferring higher expression and/or solubility and/or simpler purification, expression with molecular chaperones, expression at lower temperatures, and secretion to periplasm or medium . With all these available measures, one has to go through one by one until the problem is solved, but there is also a greater possibility that none of those will work.…”
Section: Introductionmentioning
confidence: 99%